The role of transportation of the Kyrgyz Republic in the framework of Eurasian economic union (EEAEC) cooperation (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article provides a comprehensive analysis of integration processes and dynamics of regional economic development, with a special focus on the transport sector of the Kyrgyz Republic. Given Kyrgyzstan’s strategically important geographical location at the crossroads of trade routes between Asia and Europe, its key role in ensuring efficient logistics and free movement of goods within the Eurasian Economic Union (EAEU) is examined. The article takes a detailed look at Kyrgyzstan’s transport capabilities, including the development of transport infrastructure, customs regulation and measures to simplify transit procedures.Particular attention is paid to assessing the impact of Kyrgyz transport on the economic integration of EAEU member states, as well as identifying and analyzing potential obstacles and developing strategies to overcome them. The results of the study can serve as a basis for the formation of an effective policy for the development of the transport sector, contributing to further strengthening of economic cooperation in the region.
Keywords: transport infrastructure of Kyrgyzstan, transport cooperation in the EAEU, transport corridors, transport logistics in the EAEU, globalization, logistics